Hypoglycaemic properties of Malaysian cocoa (Theobroma cacao) polyphenols-rich extract - Mohd Mokhtar, Ruzaidi Azli; Mhd Jalil, Abbe Maleyki; Ismail, Amin; Abdul Ghani, Nawalyah; Hamid, Muhajir; Mohd Bohari, Siti Pauliena; Mansor, Siti Muskinah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2008)
The objective of the study was to investigate the hypoglycaemic properties of Malaysian cocoa (Theobroma cacao) polyphenols extract in-vivo and insulin sensitivity in-vitro. Cocoa extract (CE) (containing 190-286 mg total polyphenol per gram extract) was prepared from fermented and roasted (140°C, 20 min) beans by extracting with 80% ethanol in the ratio of 1 to 10. For the in-vivo study, the CE was administered in three dosages (1%, 2%, and 3%) to groups of normal and diabetic rats for a period of 4 weeks by force-feeding. Results showed that dosages of 1% and 3% CE significantly reduced (p < 0.05) plasma glucose levels in the diabetic rats. An in-vitro study (BRIN-BD11 cell lines) was used to evaluate the effect of CE on insulin sensitivity. The results demonstrated that CE at a concentration of 0.1 mg/ml significantly increased (p < 0.05) insulin level compared to the control. The results of this study showed that Malaysian cocoa polyphenol extract have the potential of being an insulin-mimetic agent. Further studies are on-going to elucidate the underlying mechanisms of polyphenols present in CE that contribute to the reduction of plasma glucose levels and insulin mimicking activity.